Healthy diet based poverty lines - Jonas Stehl; Lutz Depenbusch; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2024)
Access to a healthy diet is a fundamental human right, yet a significant portion of the global population faces barriers to realizing this right. Conventional poverty metrics are designed around food consumption inadequate for lifelong health. We propose poverty lines based on the cost of a healthy diet and explore their key metrics such as headcount ratios and the poverty gap. According to our proposed poverty lines, 2,283 to 2,865 million people were poor in 2022, facing a shortfall of US 1,657 to US 2,370 billion per year to meet their basic needs. This is in contrast to 654 million people who are considered to live in extreme poverty according to the World Bank's conventional poverty line. Further, these poverty lines identify 286 to 868 million more people as poor compared to the Societal Poverty Line, with the majority of these individuals concentrated in South Asia and Sub-Saharan Africa.
Keywords: I32; I14; I15; N30; E20; 330; Poverty Measurement; Nutrition; Basic Needs; Healthy Diets; Welfare